Evaluating Students' Experiential Learning in International Course Program - Dinamika, Soraya Grabiella; Rahayu, Yoni; Nasution, Muhammad Muslim; Siregar , Elitaria Bestri Agustina (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
The University of Medan Area has a vision to become a university that can be recognized at the ASEAN Level, for this reason, from now on, the university has begun to prepare the students to have qualified English skills, one of which is by organizing an International Course Program, which is applied to some courses. This program was first implemented in the even semester of the 2023/2024 academic year and received high enthusiasm from the lecturers and participants. This research adopts a descriptive qualitative approach. Four courses had joined this program, which consisted of 117 participants. The data for this study was gathered using questionnaires filled out by lecturers and students. This study aimed to evaluate the students’ experiential learning in the ICP class, which peeled from the experiential learning phases designed by Wolfe & Byrne in 1975; designing, conducting, evaluating, and giving feedback. The results of this study showed that the international course program had given positive feedback on the pedagogical aspects for the students and the lecturers as well. The students could be involved in new learning experiences, and improve their English language skills, thus for the lecturers, the ICP had given additional insight into teaching methods, and curriculum development.